(untitled) (Research, Society and Development, 2020)
In a previous study, a statistical model was developed using the experimental planning technique for evaluating the influence of its variables on fluidization velocity. In this study, we investigated the Vasconcelos-statistical model (VSM) in data representation, considering fluidization with and without segregation. The methodology used was based on the simulation of the fluidization velocity of nine binary systems, comprising sand, and eight biomasses published by six authors. In addition, the results obtained using VSM were compared with those obtained using five other models, reported by different authors, but adjusted to the experimental data of these biomasses. The result obtained by the proposed models mainly indicated a discrepancy between the experimental and calculated fluidization velocities. VSM, using only three variables (particle size, particle diameter, and biomass mass fraction), yielded results of smaller discrepancy values in all simulations (2.23–12.51%), as opposed to the other comparative models, which presented more significant numbers of variables. Thus, VSM is defined as one of the most interesting models for predicting the fluidization velocity of several biomasses.